Neuroprotection by neuregulin-1 following focal stroke is associated with the attenuation of ischemia-induced pro-inflammatory and stress gene expression - Zhenfeng Xu; Gregory D. Ford; DaJoie R. Croslan; Ju Jiang; Alicia Gates; Robert Allen; Byron D. Ford (Neurobiology of Disease, 2005)
Neuregulins are a family of growth factors with potent neuroprotective properties. We recently demonstrated that neuregulin-1 blocked delayed neuronal death following focal ischemic stroke in the rat. Focal ischemia results in the release of pro-inflammatory cytokines that produce profound changes in gene expression and contribute to cell death associated with stroke. Inflammatory and stress mediators are involved in the pathogenesis of focal ischemic brain damage. We examined whether neuregulin-1 can influence inflammatory and stress gene expression in the rat brain following transient middle cerebral artery occlusion (MCAO). In this study, we compared gene expression profiles in animals treated with neuregulin-1β (NRG-1) or vehicle followed by MCAO. We used the Affymetrix GeneChip system to analyze gene expression in focal ischemia of the rat brain. Several inflammatory and stress genes were significantly induced following MCAO compared to sham controls including heat shock protein-70 (HSP70), interleukin-1β, and macrophage chemotattractant protein-1 (JE/MCP-1). Treatment with NRG-1 attenuated the expression of many of these genes by 50% or more. In vitro studies demonstrated that NRG-1 suppressed inflammatory gene expression in activated macrophages. NRG-1 also prevented neuronal death induced by oxygen-glucose deprivation in a rat neuroblastoma cell line, suggesting that NRG-1 may have both direct and indirect neuroprotective capacity. These results demonstrate that NRG-1 can regulate inflammatory and stress gene expression and may give new insight to the molecular mechanisms involved in the neuroprotective role of neuregulins in stroke.